Sectoral Growth Analysis in Determining the Okun’s Law in Indonesia - Suparta, I Made (Archives of Business Research, 2023)
This study aims to analyze the effects of agricultural sector growth, industrial sector growth, and service sector growth on economic growth, analyze the effects of agricultural sector growth, industrial sector growth, service sector growth, and economic growth on the unemployment rate, as well as analyze the indirect effects of agriculture sector growth, industrial sector growth, and service sector growth through economic growth on the unemployment rate. Using panel data in Indonesia for the 2017-2022 period. Analyzed with Smart PLS, the results of the analysis show that the growth of the agricultural sector, the growth of the industrial sector, and the growth of the services sector have a significant positive impact on economic growth. Directly, growth in the agricultural sector and growth in the services sector have a significant negative impact on the unemployment rate. while the growth of the industrial sector has no significant negative impact, and economic growth has no significant positive impact on the unemployment rate. Indirectly, the growth of the agricultural sector, the growth of the industrial sector, and the growth of the service sector have a not significant positive impact on the unemployment rate. The enactment of Okun’s Law on the impact of agricultural sector growth, industrial sector growth, and service sector growth on the unemployment rate. The inapplicability of Okun’s Law on the impact of economic growth on the unemployment rate.